ANALYSIS OF ECONOMIC ON ENVIRONMENTAL DEGRADATION IN INDONESIA - Yuswinarto, Rahardyan Haris; Gunanto, Edy Yusuf Agung (Buletin Studi Ekonomi, 2021)
Environmental degradation occurs is influenced by economic growth and the means of transportation that support it, besides that, the population size also affects the occurrence of environmental degradation. This study aims to determine the effect of economic growth, population growth and total of transportation on environmental degradation in short and long term. This research uses dynamic time series autoregressive distribution lag method. The results showed that the gross domestic product (GDP) variable had a significant positive effect in increasing CO2 gas emissions both in the short and long term. The variable amount of transportation has a positive and insignificant effect on the increase in CO2 gas emissions in the short term and has a negative effect in the long term. Meanwhile, population growth variable has a positive and significant effect in the short term and negative and significant in the long term.